EVALUASI APLIKASI DEPOK SINGLE WINDOW DALAM PENERAPAN KONSEP SMART CITY DI KOTA DEPOK - Irsad Rakha Chandra, Muhammad; Djumiarti, Titik; Afrizal, Teuku (Journal of Public Policy and Management Review, 2024)
Depok Single Window application was developed by Diskominfo Kota Depok as an effort to implement smart governance in smart city concept in Depok City. This application offers 145 types of services within a single window, but there are still several challenges in implementation, such as frequent errors, a high number of negative reviews, and an insufficient workforce in the implementing unit. This research aims to analyze the evaluation results and the inhibiting factors affecting Depok Single Window application in the smart city implementation in Depok City. This research used descriptive qualitative method, with data collected through non-participatory observation, interviews, and documentation to present the phenomenon factually and in-depth in 2024. Informants were selected by purposive sampling, and application users were chosen through incidental sampling. The theory used in this research is William Dunn's evaluation theory, with the addition of four criteria to analyze the inhibiting factors. The results of the study show that indicators of efficiency, adequacy, equity, and accuracy still need to be addressed for the application to function effectively. The inhibiting factors affecting the effectiveness of the Depok Single Window application include resource factors, communication, and bureaucratic structure. Based on the research findings, the recommendations provided to address the identified problems include the establishment of technical work guidelines and proper division of tasks within the implementing unit, the development of a regular application maintenance schedule, periodic dissemination of information related to the application, and coordination of all relevant regional apparatus to help ensure the success of the application.